1995
DOI: 10.1128/jb.177.7.1864-1871.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an endo-beta-1,6-glucanase from Trichoderma harzianum that is related to its mycoparasitism

Abstract: The enzymes from Trichoderma species that degrade fungal cell walls have been suggested to play an important role in mycoparasitic action against fungal plant pathogens. The mycoparasite Trichoderma harzianum produces at least two extracellular ␤-1,6-glucanases, among other hydrolases, when it is grown on chitin as the sole carbon source. One of these extracellular enzymes was purified to homogeneity after adsorption to its substrate, pustulan, chromatofocusing, and, finally, gel filtration. The apparent molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 53 publications
6
70
0
Order By: Relevance
“…Our findings are similar to those obtained with Saccharomyces cerevisiae and T. harzianum, which also produced both endo-and exo-β-1,3-glucanases (10,18,24). Our findings are similar to those obtained with Saccharomyces cerevisiae and T. harzianum, which also produced both endo-and exo-β-1,3-glucanases (10,18,24).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are similar to those obtained with Saccharomyces cerevisiae and T. harzianum, which also produced both endo-and exo-β-1,3-glucanases (10,18,24). Our findings are similar to those obtained with Saccharomyces cerevisiae and T. harzianum, which also produced both endo-and exo-β-1,3-glucanases (10,18,24).…”
Section: Discussionsupporting
confidence: 90%
“…is due to the presence of hydrolytic enzymes, including chitinases (Carsolio et al, 1999;De La Cruz et al, 1995;Flores et al, 1997;Peterbauer et al, 1996;Thrane et al, 1997). Hadar et al (1979) showed that T. harzianum, under greenhouse conditions, when applied in the form of wheat bran culture to R. solani-infested soil, effectively controlled damping-off in bean, tomato and eggplant seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported biocontrol agents are species of Trichoderma (Bell et al 1982, Ordentlich et al 1991, of which T. harzianum is reported to be especially effective (de la Cruze et. al.…”
Section: Nurserymentioning
confidence: 99%